Burnout Investigation of Small Diameter Tubes Immersed in Nanofluids - Janusz T. Cieśliński; Katarzyna Ronewicz (Energies, 2021)
This paper deals with research into pool boiling critical heat flux (CHF) of water–Al2O3, water–TiO2 and water–Cu nanofluids on horizontal stainless steel tubes. The experiments were conducted under atmospheric pressure. Nanoparticles were tested at concentrations of 0.001%, 0.01%, 0.1% and 1% by weight. Ultrasonic vibration was used in order to stabilize the dispersion of the nanoparticles. Although dispersants were not used to stabilize the suspension, the solutions tested showed satisfactory stability. Experimental measurements were performed with stainless steel tubes of three outside diameters: 1.6, 3 and 5 mm. Enhancement of CHF was observed to be independent of the concentration and material of the nanoparticles and tube diameter, with simultaneous heat transfer degradation. Built up during the boiling process, nanolayers improve substantially the heating surface wettability. A correlation is suggested for the CHF prediction during pool boiling of nanofluids.